Comparative Biogas production by Anaerobic Digestion Using Sugarcane Bagasse, Cow Dung and Chicken Droppings Obtained from Katsina Metropolis as Substrates - Abdulhamid Mohammed; Muazu Batagarawa; Kamaluddeen Kabir (UMYU Journal of Microbiology Research)
The use of energy derived from fossil raw materials as conventional primary source of energy has led to environmental pollution climate changes. The need for other alternative sources such as energy derived from wind, solar and biofuel has become necessary. This research investigated the generation of biogas from three types of wastes: Sugarcane bagasse, Cow dung, and chicken droppings wastes using three different biogas plants. Batch operation was carried out and the daily gas produced from each digester was monitored for the retention period of four weeks at the ambient and slurry temperatures. The digesters were charged differently with these wastes in the ratio of 1:3 wastes to distilled water. The ambient temperature ranges within the retention period were 17-290C and a slurry temperature range of 19-320C. The result showed that chicken droppings had the highest cumulative biogas yield of 3228.3cm3; cow dung had 2816.6cm3 and sugarcane bagasse had the least cumulative production of 681.4cm3 within digestion period of 30 days. The qualitative test of the generated gas showed that, cow dung has superior quality for biogas production with the highest methane content of 61.3% over the sugarcane bagasse (57.2%) and chicken droppings (47.6%). The bacterial enumeration for chicken droppings was discovered to have highest count of 28.7 x 105cfu/g than cow dung and sugarcane bagasse with 21.2 x 105cfu/g and 2.1 x 105cfu/g respectively. Cow dung was discovered to have the highest total solid content of 84.74% while sugarcane bagasse had the least (8.67%). The utilization of these waste stockscould bean alternative option for energy source and wastes treatment.